A survey of Chinese pharmacists participating in anti‐infective therapy and its related information technology support. (13th May 2020) - Wang, Yanting; Dai, Yuanyuan; Yang, Jun; Zhou, Haiyan; Chen, Zhe; Li, Guohui
Abstract: What is known and objective: Anti‐infective therapy is the major daily work for most clinical pharmacists in China, and information technology (IT) support for them is very important. However, the current situation of pharmacists' roles in anti‐infective therapy and related IT support are seldom reported. The aim of the study was to investigate the current situation of pharmacists participating in anti‐infective therapy and the corresponding hospital IT support, which may help identify and solve related problems and facilitate pharmacists to play better roles. Methods: A 15‐item questionnaire was distributed online to clinical pharmacists from Chinese hospitals. Pharmacists answered the questions on the WeChat platform. Data were analysed using descriptive statistics. Results and discussion: A total of 272 valid questionnaires were returned, and the respondents were from 27 provinces (or autonomous regions or municipalities) of China covering over 15 specialties. Most of the respondents (76.1%) were from tertiary hospitals and 72.4% of all the respondents participated in anti‐infective therapy. They mainly performed drug selection (95.4%), dose adjustment (88.8%) and adverse drug reaction monitoring (84.8%) for anti‐infective therapy, in ways such as consultation (71.1%), drug consult (86.3%) and prescription evaluation (88.8%). Most pharmacists (93.0%) thought that the modules of anti‐infective therapy in hospital IT system needed to be advanced, in the aspects of doctor‐pharmacist interaction, convenience for pharmacists to control drug expenses and integration of multi‐functions for anti‐infective therapy. What is new and conclusion: The roles of Chinese clinical pharmacists in anti‐infective therapy are becoming increasingly clear, and establishing smart, pharmacist‐friendly and highly‐integrated electronic interfaces will facilitate the establishment of pharmacist‐driven anti‐infective therapy team, thus improving work efficiency and user experience. Abstract : The roles of Chinese clinical pharmacists in anti‐infective therapy are becoming increasingly clear, but there needs to be efforts to establish smart, pharmacist‐friendly and highly‐integrated electronic interfaces in hospital IT systems.